Conductive paste, electrode prepared therefrom, and crystalline silicon solar cell comprising the electrode

By adding laser heat accelerator and sintering treatment to the conductive paste, combined with laser enhancement contact optimization process, the problem of high contact resistance of solar cells is solved and the efficiency of the battery is improved.

CN118213104BActive Publication Date: 2025-02-11HERAEUS PHOTOVOLTAICS TECHNOLOGY (SHANGHAI) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410061977.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-16
Publication Date
2025-02-11
Estimated Expiration
2044-01-16

AI Technical Summary

Technical Problem

The contact resistance of existing solar cells is high, which affects battery efficiency.

Method used

The laser heat accelerator ZrxCuyAlmNizNbnAq is added to the conductive paste, and the electrode is formed by sintering treatment, and the electrode contact performance is further optimized using the laser enhancement contact optimization process.

Benefits of technology

The contact resistance of solar cells is reduced, and the conversion efficiency and filling factor of solar cells are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004666853420000241
    Figure BDA0004666853420000241
  • Figure BDA0004666853420000251
    Figure BDA0004666853420000251
  • Figure BDA0004666853420000252
    Figure BDA0004666853420000252
Patent Text Reader

Abstract

The present invention relates to a conductive paste, which comprises: a) conductive metal particles, b) glass powder, c) laser thermal accelerator and d) organic carrier, wherein the laser thermal accelerator is represented by formula (I): Zr x Cu y Al m Ni z Nb n A q (I), wherein x=10-90 wt%, y=5-50 wt%, m=0.5-10 wt%, z=0-20 wt%, n=0-15 wt%, q=0-5 wt%, and A is a metal selected from Ag, Cr, Zn and Ti, and the weight percentage is based on the weight of the laser thermal accelerator. The present invention further relates to an electrode formed by sintering the conductive paste and a crystalline silicon solar cell comprising a substrate and the electrode bonded to the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a conductive paste, an electrode prepared from the conductive paste and a crystalline silicon solar cell comprising the electrode. Background Art

[0002] Solar energy is an attractive green energy source because it is sustainable and only produces non-polluting byproducts, so people have developed solar cells that use the photovoltaic effect to convert solar energy into electrical energy. Solar cells are usually made of semiconductive materials, such as appropriately doped silicon materials. When light shines on the solar cell, a portion of the incident light is reflected by the surface, and the remaining portion of the incident light is transmitted to the solar cell. The transmitted photons are absorbed by the solar cell, which in turn excites the electrons of the semiconductive material to generate electron-hole pairs, and the electrons and holes are guided through the electrodes located on the front side of the substrate (i.e., the side illuminated by light) and the electrodes on the reverse side (i.e., the side not illuminated by light) to form current, thereby obtaining electrical energy.

[0003] The front electrode of a solar cell is usually arranged in two sets of perpendicular straight lines, called "grid lines" and "bus bars". The grid lines make electrical contact with the front side, while the bus bars connect these grid lines, allowing efficient extraction of charge into the external circuit. For this arrangement of grid lines and bus bars, it is usually applied in the form of a conductive paste, which is fired to form a solid electrode body. The back electrode of the solar cell is usually also applied in the form of a conductive paste, which is then fired to obtain a solid electrode body.

[0004] The quality of the conductive paste will directly affect the performance of the electrode material, such as contact resistance. A typical conductive paste contains conductive metal particles, glass powder and organic carriers, where the conductive metal particles form a metal semiconductor ohmic contact with the underlying silicon, which is directly responsible for the transmission of current from the silicon emitter region to the gate line. Therefore, whether the conductive paste can obtain a low contact resistance with the silicon emitter region has an important impact on the performance of solar cells.

[0005] CN101609849A discloses a silver conductor paste for the front electrode of a solar cell and a preparation process thereof, wherein the silver paste for the front electrode of the solar cell uses silver powder of different particle size ranges as the conductive functional phase. The spherical silver powder of two particle size ranges is mixed and used to fill the small-particle silver powder in the gap of the large-particle silver powder, and a more compact conductive network can be formed after the electrode is formed, thereby reducing the contact resistance of the battery and improving the electrical performance and conversion efficiency. In addition, by adding BaO and CaO powders, the glass phase is microcrystallized during the sintering process, the supersaturation of dissolved silver in the glass phase is increased, and more crystallized silver is precipitated at the Ag-Si interface to form a good ohmic contact, thereby reducing the contact resistance. However, the results in Table 1 of CN101609849A show that the contact resistance of its embodiment is higher than that of the comparative example.

[0006] CN115312629A discloses a solar cell and a method for preparing the same, wherein the metal paste on the front side of the silicon wafer is processed by laser enhanced contact optimization technology to form a local contact electrode with ohmic contact on the front side of the silicon wafer to reduce the contact resistance. However, CN115312629A does not provide corresponding test data to prove that the contact resistance can be reduced.

[0007] Therefore, there is still a need to further find a method for reducing the contact resistance of solar cells to improve the efficiency of solar cells. Summary of the invention

[0008] In order to reduce the contact resistance of solar cells, the present invention provides a conductive paste comprising:

[0009] a) Conductive metal particles,

[0010] b) glass powder,

[0011] c) laser thermal accelerator, and

[0012] d) an organic carrier,

[0013] The laser thermal accelerator is represented by formula (I):

[0014] Zr x Cu y Al m Ni z Nb n A q (I)

[0015] In formula (I), x=10-90 wt%, y=5-50 wt%, m=0.5-10 wt%, z=0-20 wt%, n=0-15 wt%, q=0-5 wt%, and A is a metal selected from Ag, Cr, Zn and Ti, and the weight percentages are based on the weight of the laser thermal accelerator.

[0016] The present invention also provides an electrode for a crystalline silicon solar cell, which is formed by sintering the conductive paste.

[0017] The present invention also provides a crystalline silicon solar cell, which comprises a substrate and the electrode combined on the substrate.

[0018] The applicant has found that the contact resistance of a solar cell can be reduced by adding a laser thermal accelerator to a conductive paste, and thus the efficiency of the solar cell prepared using the conductive paste can be improved. DETAILED DESCRIPTION

[0019] Conductive paste

[0020] According to the present invention, the conductive paste is applied to the surface of the solar cell wafer and forms a solid electrode body in electrical contact with the surface when fired. According to the present invention, the conductive paste comprises:

[0021] a) Conductive metal particles,

[0022] b) glass powder,

[0023] c) laser thermal accelerator, and

[0024] d) an organic carrier,

[0025] The laser thermal accelerator is represented by formula (I):

[0026] Zr x Cu y Al m Ni z Nb n A q (I)

[0027] In formula (I), x=10-90 wt%, y=5-50 wt%, m=0.5-10 wt%, z=0-20 wt%, n=0-15 wt%, q=0-5 wt%, and A is a metal selected from Ag, Cr, Zn and Ti, preferably Ti, and the weight percentages are based on the weight of the laser thermal accelerator.

[0028] In a preferred embodiment, the conductive paste comprises:

[0029] a) Conductive metal particles,

[0030] b) glass powder,

[0031] c) laser thermal accelerator, and

[0032] d) an organic carrier,

[0033] The laser thermal accelerator is represented by formula (I):

[0034] Zr x Cu y Al m Ni z Nb n A q (I)

[0035] In formula (I), x=50-90 wt%, y=5-35 wt%, m=0.5-10 wt%, z=0-20 wt%, n=0-15 wt%, q=0-5 wt%, and A is a metal selected from Ag, Cr, Zn and Ti, preferably Ti, and the weight percentages are based on the weight of the laser thermal accelerator.

[0036] a) Conductive metal particles

[0037] The conductive metal particles present in the conductive paste provide metallic conductivity to the solid electrode formed when the conductive paste is sintered. Metal particles that are conducive to efficient sintering and obtain electrodes with high conductivity and low contact resistance are preferred. All metal particles known to those skilled in the art and considered suitable in the context of the present invention can be used as conductive metal particles in the conductive paste.

[0038] According to the present invention, preferred electrically conductive metal particles are metals, alloys, mixtures of at least two metals, mixtures of at least two alloys or mixtures of at least one metal and at least one alloy.

[0039] According to the present invention, the conductive metal particles may include Ag, Al, Cu, Zn, Pd, Ni, Pb, Au or a combination thereof, preferably Ag, Al, Cu or an alloy thereof, more preferably Ag. In a preferred embodiment of the present invention, the conductive metal particles are silver particles (silver powder).

[0040] According to the present invention, when the conductive metal particles are alloys, the conductive metal particles may be crystalline metal particles or amorphous metal particles, preferably amorphous metal particles.

[0041] According to the present invention, the conductive metal particles can have various shapes, surfaces, sizes, surface area to volume ratios, oxygen content and oxide layers. Many shapes are known to those skilled in the art. Some examples are spherical, angular, elongated (rod-like or needle-like) and flat (sheet-like). Metal particles can also exist as a combination of particles of different shapes. According to the present invention, metal particles having a shape or a combination of shapes that are conducive to favorable sintering, electrical contact, adhesion and conductivity of the prepared electrode are preferred. Without considering the surface characteristics, a way to characterize such shapes is by means of the parameters length, width and thickness. For the purposes of the present invention, the length of the particle is given by the length of the longest spatial displacement vector whose two endpoints are contained in the particle. The width of the particle is given by the length of the longest spatial displacement vector perpendicular to the length vector defined above and whose two endpoints are contained in the particle. The thickness of the particle is given by the length of the longest spatial displacement vector perpendicular to the length vector and width vector defined above and whose two endpoints are contained in the particle. In one embodiment of the present invention, metal particles having a shape that is as uniform as possible, i.e. a shape in which the ratios involving length, width and thickness are as close to 1 as possible, preferably all ratios are in the range of 0.7-1.5, more preferably 0.8-1.3, most preferably 0.9-1.2. In one embodiment of the present invention, preferred shape examples of the conductive metal particles are spheres and cubes or a combination thereof, or a combination of one or more thereof with other shapes. In one embodiment of the present invention, the conductive metal particles in the conductive paste are spherical.

[0042] The particle size D50 is a particle characteristic known to those skilled in the art. The determination of the particle size D50 is known to those skilled in the art. According to the present invention, the particle size D50 of the conductive metal particles is preferably 0.5-10 μm, such as 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, preferably 1-5 μm.

[0043] In one embodiment of the present invention, the conductive metal particles are silver particles (silver powder) having a particle size D50 of 1-4 μm, preferably 2-3.5 μm, more preferably 2.8-3.2 μm.

[0044] In another embodiment of the present invention, the conductive metal particles are aluminum particles (aluminum powder) having a particle size D50 of 1-5 μm, preferably 2-4 μm, more preferably 2.5-3.5 μm.

[0045] In yet another embodiment of the present invention, the conductive metal particles are copper particles (copper powder) having a particle size D50 of 1-6 μm, preferably 2-4 μm, more preferably 2-3 μm.

[0046] In one embodiment of the present invention, the conductive metal particles are present in a proportion of greater than 50 wt %, preferably greater than 70 wt %, and most preferably greater than 80 wt % of the conductive paste.

[0047] In a preferred embodiment of the present invention, the conductive metal particles are present in a proportion of 50-95 wt % of the conductive paste, for example 50 wt %, 60 wt %, 70 wt %, 80 wt %, 90 wt %.

[0048] b) Glass powder

[0049] According to the present invention, glass powder is present in the conductive paste to cause etching and sintering. For the purposes of the present invention, it is preferred that the glass powder is an amorphous or partially crystalline solid with a low glass transition temperature Tg. The glass transition temperature Tg is the temperature at which a rigid solid is transformed into a partially flowing, undercooled melt when heated. Methods for determining the glass transition temperature Tg are well known to those skilled in the art. Etching and sintering caused by the glass powder occur above the glass transition temperature Tg of the glass powder, and preferably the glass transition temperature Tg is lower than the desired peak firing temperature.

[0050] All glass powders known to those skilled in the art and considered suitable in the context of the present invention can be used as glass powder in the conductive paste. For the purposes of the present invention, the glass powder present in the conductive paste preferably comprises an element, an oxide thereof, a compound that produces an oxide upon heating, or a mixture thereof. For this purpose, preferred elements are Si, B, Al, Bi, Li, Na, K, Mg, Pb, Zn, Gd, Ce, Zr, Ti, Mn, Sn, Ru, Co, Fe, Cu, Ba, Cr, Te, P, or a combination thereof. For the purposes of the present invention, the preferred oxides that the glass powder may comprise are alkali metal oxides, alkaline earth metal oxides, rare earth oxides, oxides of elements of groups V and VI, other oxides, or a combination thereof. Further, preferred oxides include lead oxide (PbO), boron oxide (B2O3), silicon dioxide (SiO2), zinc oxide (ZnO), aluminum oxide (Al2O3), tellurium oxide (TeO2), bismuth oxide (Bi2O3), phosphorus oxide (P2O5), and a combination thereof. Preferred oxides are also mixed oxides containing at least two of the elements listed as preferred elemental constituents of the glass frit, or mixed oxides formed by heating at least one of the above-mentioned oxides with at least one of the above-mentioned metals. For the purposes of the present invention, mixtures of at least two of the above-mentioned oxides and mixed oxides are also preferred.

[0051] In one embodiment of the present invention, the glass powder may include:

[0052] 30-50 mol% PbO;

[0053] 5-15 mol % B2O3; and

[0054] 40-60 mol% SiO2,

[0055] The mole percentages stated are based on the total moles of all oxides.

[0056] In one embodiment of the present invention, the glass powder may include:

[0057] 20-30 mol% PbO;

[0058] 10-20 mol% B2O3;

[0059] 40-50 mol% SiO2;

[0060] 2-8 mol% ZnO;

[0061] 2-8 mol% Al2O3; and

[0062] 2-8 mol% Bi2O3,

[0063] The mole percentages stated are based on the total moles of all oxides.

[0064] In one embodiment of the present invention, the glass powder may include:

[0065] 20-40 mol% PbO;

[0066] 2-8 mol% SiO2;

[0067] 10-20 mol % ZnO; and

[0068] 40-60 mol% TeO2,

[0069] The mole percentages stated are based on the total moles of all oxides.

[0070] In one embodiment of the present invention, the glass powder may include:

[0071] 30-50 mol% PbO;

[0072] 2-8 mol% SiO2;

[0073] 2-8 mol % ZnO; and

[0074] 40-60 mol% TeO2,

[0075] The mole percentages stated are based on the total moles of all oxides.

[0076] In one embodiment of the present invention, the glass powder may include:

[0077] 5-15 mol % B2O3;

[0078] 30-50 mol% SiO2;

[0079] 10-20 mol% ZnO;

[0080] 20-40 mol% Bi2O3; and

[0081] 1-5 mol% P2O5,

[0082] The mole percentages stated are based on the total moles of all oxides.

[0083] According to the present invention, the glass powder preferably has a glass transition temperature Tg lower than the required firing temperature of the conductive paste. In one embodiment of the present invention, the glass powder preferably has a glass transition temperature Tg of 300-600°C, more preferably 300-500°C, most preferably 320-450°C.

[0084] According to the present invention, the glass powder particles can have various shapes, surface properties, sizes, surface area to volume ratios, and coatings. Many shapes of glass powder particles are known to those skilled in the art. Some examples are spherical, angular, elongated (rod-like or needle-like), and flat (flake-like). Glass powder particles can also be present as a combination of particles of different shapes. According to the present invention, glass powder having a shape or a combination of shapes that facilitates favorable sintering, adhesion, electrical contact, and conductivity of the resulting electrode is preferred.

[0085] According to the present invention, the particle size D50 of the glass powder is preferably 0.1-10 μm, more preferably 0.2-7 μm, and most preferably 0.5-5 μm. The determination of the particle size D50 is well known to those skilled in the art.

[0086] In one embodiment of the present invention, the glass powder has a particle size D50 of 0.1-3 μm, preferably 0.5-2 μm, more preferably 0.8-1.5 μm.

[0087] In one embodiment of the present invention, the glass powder is present in a proportion of 0.1-15 wt %, preferably 3-10 wt %, of the conductive paste.

[0088] In one embodiment of the present invention, the glass powder of the present invention can be prepared by the following method and then used to prepare the conductive paste of the present invention: all components of the glass powder are combined together to obtain a composition, the composition is melted to obtain a glass frit, and the composition is quenched in deionized water, and finally the product is made into particles with a desired particle size to obtain the glass powder of the present invention.

[0089] Preferably, the “melting” is performed by charging the composition into a crucible, placing the crucible in a muffle furnace and melting the composition at a high temperature; the “water quenching” is performed by removing the molten glass from the muffle furnace and pouring it into a bucket filled with deionized water; and the “forming particles having a desired particle size” is performed by grinding the water-quenched glass slag with a ball mill to obtain glass powder having a desired particle size D50.

[0090] In the above method, the temperature of the muffle furnace is high enough to melt the components of the glass powder, and the melting time is long enough to uniformly mix the components.

[0091] More preferably, in the preparation of the glass powder, the temperature of the muffle furnace is 800-1500° C., preferably 900-1200° C., and the melting time of the mixture is 15 minutes to 2 hours, preferably 30 minutes to 1 hour.

[0092] In another embodiment of the present invention, the glass powder of the present invention can be prepared by the following method and then used to prepare the conductive paste of the present invention: combining part of the components of the glass powder together to obtain a first composition, melting the first composition to obtain glass, quenching in deionized water, and finally making the product into first particles with a desired particle size; combining the remaining components of the glass powder together to obtain a second composition, melting the second composition to obtain glass, quenching in deionized water, and finally making the product into second particles with a desired particle size; combining the first particles and the second particles together to obtain the glass powder of the present invention.

[0093] The glass powder of the present invention can be divided into further parts and obtained by corresponding methods.

[0094] For example, in yet another embodiment of the present invention, the glass powder of the present invention can be prepared by the following method, and then used to prepare the conductive paste of the present invention: the first part of the components of the glass powder are combined together to obtain a first composition, the first composition is melted to obtain glass, and the product is quenched in deionized water, and finally the product is made into first particles with a desired particle size; the second part of the components of the glass powder are combined together to obtain a second composition, the second composition is melted to obtain glass, and the product is quenched in deionized water, and finally the product is made into second particles with a desired particle size; the remaining components of the glass powder are combined together to obtain a third composition, the third composition is melted to obtain glass, and the product is quenched in deionized water, and finally the product is made into third particles with a desired particle size; the first particles, the second particles, and the third particles are combined together to obtain the glass powder of the present invention.

[0095] Obviously, the above first particles, second particles and / or third particles etc. can be particles that have been prepared.

[0096] c) Laser thermal accelerator

[0097] According to the present invention, the laser thermal accelerator is represented by formula (I):

[0098] Zr x Cu y Al m Ni z Nb n A q (I)

[0099] In formula (I), x=10-90 wt%, y=5-50 wt%, m=0.5-10 wt%, z=0-20 wt%, n=0-15 wt%, q=0-5 wt%, and A is a metal selected from Ag, Cr, Zn and Ti, preferably Ti, and the weight percentages are based on the weight of the laser thermal accelerator.

[0100] In one embodiment of the present invention, in formula (I), x = 10-90 weight%, for example, x = 10 weight%, 20 weight%, 30 weight%, 40 weight%, 50 weight%, 60 weight%, 70 weight%, 80 weight%, 90 weight%, preferably 50-90 weight%, more preferably 65-85 weight%, and the weight percentages are based on the weight of the laser thermal accelerator.

[0101] In one embodiment of the present invention, in formula (I), y=5-50 weight%, for example y=5 weight%, 10 weight%, 15 weight%, 20 weight%, 25 weight%, 30 weight%, 35 weight%, 40 weight%, 45 weight%, 50 weight%, preferably 5-35 weight%, more preferably 10-30 weight%, and the weight percentages are based on the weight of the laser thermal accelerator.

[0102] In one embodiment of the present invention, in formula (I), m = 0.5-10 wt%, for example m = 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, preferably 2-9 wt%, and the weight percentages are based on the weight of the laser thermal accelerator.

[0103] In one embodiment of the present invention, in formula (I), z = 0-20 weight%, for example z = 0.5 weight%, 1 weight%, 2 weight%, 3 weight%, 4 weight%, 5 weight%, 6 weight%, 7 weight%, 8 weight%, 9 weight%, 10 weight%, 11 weight%, 12 weight%, 13 weight%, 14 weight%, 15 weight%, 16 weight%, 17 weight%, 18 weight%, 19 weight%, 20 weight%, preferably 8-15 weight%, and the weight percentages are based on the weight of the laser thermal accelerator.

[0104] In one embodiment of the present invention, in formula (I), n = 0-15 weight%, for example n = 0.5 weight%, 1 weight%, 2 weight%, 3 weight%, 4 weight%, 5 weight%, 6 weight%, 7 weight%, 8 weight%, 9 weight%, 10 weight%, 11 weight%, 12 weight%, 13 weight%, 14 weight%, 15 weight%, preferably 1-10 weight%, and the weight percentages are based on the weight of the laser thermal accelerator.

[0105] In one embodiment of the present invention, in formula (I), q = 0-5% by weight, for example, q = 0.5% by weight, 1% by weight, 2% by weight, 3% by weight, 4% by weight, 5% by weight, preferably 1-5% by weight, and the weight percentages are based on the weight of the laser thermal accelerator.

[0106] In one embodiment of the present invention, the laser thermal accelerator is amorphous (non-crystalline) metal alloy particles.

[0107] In one embodiment of the present invention, the laser thermal accelerator is an amorphous metal alloy particle having a particle size D50 of 0.1-8 μm, for example 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm. In a preferred embodiment of the present invention, the laser thermal accelerator is an amorphous metal alloy particle having a particle size D50 of 1-5 μm. The determination of particle size D50 is well known to those skilled in the art.

[0108] In one embodiment of the present invention, the laser thermal accelerator is present in a proportion of 0.05-10 wt % of the conductive paste, for example, 0.05 wt %, 0.1 wt %, 0.5 wt %, 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, preferably 0.1-1 wt %, more preferably 0.1-0.5 wt %.

[0109] In one embodiment of the present invention, the laser thermal accelerator is prepared by a jet powder preparation method, which comprises the following steps:

[0110] (1) mixing and evenly dispersing the high-purity metal powders used to prepare the laser thermal accelerator according to the formula ratio;

[0111] (2) heating and melting the obtained metal powder mixture in a crucible (e.g., a copper pressure crucible lined with quartz) at a temperature of >1000° C. to obtain a liquid master alloy;

[0112] (3) Under the action of pressure, the liquid master alloy is directly sprayed into ice water mixed with NaCl to obtain amorphous LTP alloy powder.

[0113] According to one embodiment of the present invention, the high-purity metal powder in step (1) has a purity of, for example, 99% or more.

[0114] According to one embodiment of the present invention, the temperature of step (2) is preferably 1050-1500°C, such as 1100°C, 1200°C, 1300°C, 1400°C.

[0115] According to one embodiment of the present invention, the pressure of step (3) is preferably 20-100 PSI, for example 30 PSI, 40 PSI, 50 PSI, 60 PSI, 70 PSI, 80 PSI, 90 PSI.

[0116] According to one embodiment of the present invention, the NaCl concentration in step (3) is preferably 1-10 wt %, such as 2-5 wt % or 6-9 wt %.

[0117] According to the present invention, LTP powders with different particle sizes and morphologies can be obtained by adjusting the temperature, pressure and injection speed.

[0118] d) Organic carrier

[0119] In one embodiment of the present invention, the conductive paste comprises an organic vehicle commonly used in the art.Preferred organic vehicles are those that provide optimal stability of the ingredients within the conductive paste and impart viscosity to the conductive paste that allows for effective printability.

[0120] In one embodiment, the amount of the organic vehicle may be 2-20 wt %, more preferably 5-15 wt %, and most preferably 6-10 wt %, based on the total weight of the conductive paste.

[0121] In one embodiment, the organic vehicle comprises a solvent, a binder (e.g., an organic binder, such as a polymer, a resin), a surfactant, an additive, or any combination thereof, preferably an organic binder and a solvent. The additive comprises a thixotropic agent, a viscosity modifier, a stabilizer, a thickener, an emulsifier, a dispersant, a slip agent (e.g., an alkyl-modified silicone oil), or a pH modifier, and any combination thereof. For example, in one embodiment, the organic vehicle comprises one or more binders in an organic solvent.

[0122] The binder may be present in an amount of 0.1-10 wt %, preferably 0.1-8 wt %, more preferably 0.5-7 wt %, based on the total weight of the organic vehicle. Preferred binders are those that promote the formation of conductive pastes having favorable stability, printability, viscosity and sintering properties. Preferred binders (which generally fall within the category referred to as "resins") are polymeric binders, monomeric binders, and binders that are combinations of polymers and monomers. The polymeric binder may also be a copolymer.

[0123] Preferred polymeric binders include binders carrying functional groups in the polymer backbone, binders carrying functional groups outside the backbone, and binders carrying functional groups inside and outside the backbone. Preferred polymers carrying functional groups in the backbone include, for example, polyesters, substituted polyesters, polycarbonates, substituted polycarbonates, polymers carrying cyclic groups in the backbone, polysaccharides, substituted polysaccharides, polyurethanes, substituted polyurethanes, polyamides, substituted polyamides, phenolic resins, substituted phenolic resins, copolymers of one or more monomers of the above polymers (optionally with other comonomers) or combinations of at least two thereof.

[0124] Preferred polymers carrying cyclic groups in the main chain include, for example, polyvinyl butyral (PVB) and its derivatives and polyterpineol and its derivatives or mixtures thereof. Preferred polysaccharides include, for example, cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, propyl cellulose, hydroxypropyl cellulose, butyl cellulose, derivatives thereof and mixtures of at least two thereof. Other preferred polymers include, for example, cellulose ester resins, such as cellulose acetate propionate, cellulose acetate butyrate and any combination thereof. Other preferred polymers are those disclosed in U.S. Patent Application Publication No. 2013 / 0180583, which is incorporated herein by reference.

[0125] Preferred polymers carrying functional groups outside the polymer backbone are polymers carrying amide groups, polymers carrying acid and / or ester groups (commonly referred to as acrylic resins) or polymers carrying a combination of the above functional groups or a combination thereof. Preferred polymers carrying amide groups outside the backbone include, for example, polyvinyl pyrrolidone (PVP) and its derivatives. Preferred polymers carrying acid and / or ester groups outside the backbone include, for example, polyacrylic acid and its derivatives, polymethyl methacrylate (PMMA) and its derivatives or mixtures thereof.

[0126] Preferred monomeric binders include, for example, monomeric binders based on ethylene glycol. Preferred monomeric binders based on ethylene glycol are binders having multiple ether groups, multiple ester groups, or binders having one ether group and one ester group, preferred ether groups are methyl, ethyl, propyl, butyl, pentyl, hexyl and higher alkyl ethers, preferred ester groups are acetates and their alkyl ether derivatives, preferably ethylene glycol monobutyl ether monoacetate or mixtures thereof.

[0127] Preferred binders in the present invention are, for example, alkylcelluloses (preferably ethylcellulose), derivatives thereof and mixtures thereof with other binders from the previous list of binders.

[0128] The amount of the organic solvent may be 40 to 90% by weight, more preferably 35 to 85% by weight, based on the total weight of the organic vehicle.

[0129] Preferred solvents are solvents that allow the formation of an electroconductive paste having favorable viscosity, printability, stability and sintering properties. All solvents known in the art and considered suitable in the present invention can be used as solvents in the organic vehicle. According to the present invention, preferred solvents are solvents that allow a preferred high level of printability of the electroconductive paste as described above to be achieved. Preferred solvents according to the present invention are solvents that exist in liquid form at standard ambient temperature and pressure (SATP) (25°C, 100 kPa), preferably solvents having a boiling point above 90°C and a glass transition temperature Tg above -20°C.

[0130] Preferred solvents are polar or nonpolar, protic or aprotic, aromatic or nonaromatic. Preferred solvents include, for example, monoalcohols, diols, polyols, monoesters, diesters, polyesters, monoethers, diethers, polyethers, solvents comprising at least one or more of these classes of functional groups, optionally comprising other classes of functional groups, and mixtures of two or more of the above solvents, for example, diethylene glycol butyl ether acetate.

[0131] The organic vehicle may also include a surfactant. The amount of the surfactant may be 0-10 wt %, preferably 0-8 wt %, more preferably 0.01-6 wt %, based on the total weight of the organic vehicle. Preferred surfactants in the present invention are surfactants that promote the formation of conductive pastes with favorable stability, printability, viscosity and sintering properties. All surfactants known in the art and considered suitable in the present invention can be used as surfactants in the organic vehicle. Preferred surfactants may have nonionic, anionic, cationic, amphoteric or zwitterionic heads. Preferred surfactants are polymeric and monomeric or mixtures thereof.

[0132] According to the present invention, the conductive paste optionally contains additives commonly used in the art. Preferred conductive paste additives are components added to the conductive paste in addition to the ingredients that have been explicitly mentioned, which are used to promote higher performance of the conductive paste, the electrode made therefrom, or the resulting crystalline silicon solar cell. All additives known in the art and considered suitable in the present invention can be used as conductive paste additives. Preferred additives are thixotropic agents, viscosity regulators, stabilizers, thickeners, emulsifiers, dispersants, lubricants or pH regulators and any combination thereof. Preferred thixotropic agents herein are carboxylic acid derivatives, preferably fatty acid derivatives or combinations thereof. Preferred fatty acid derivatives are C9H 19 COOH (decanoic acid), C 11 H 23 COOH (lauric acid), C 13 H 27 COOH (myristic acid), C 15 H 31 COOH (palmitic acid), C 17 H 35 COOH(stearic acid), C 18 H 34 O2(oleic acid), C 18 H 32 O2 (linoleic acid), castor oil, hydrogenated castor oil or a combination thereof.

[0133] In one embodiment of the present invention, to form a conductive paste, glass powder can be combined with conductive metal particles, laser thermal accelerators, organic vehicles, and optional conductive paste additives using any method known in the art for preparing a paste. The details of the preparation method are not critical, as long as it produces a homogeneously dispersed paste. The components can be mixed, for example, with a mixer and then passed through, for example, a three-roll mill to make a dispersed, uniform paste.

[0134] Electrodes for crystalline silicon solar cells

[0135] The electrode for the crystalline silicon solar cell of the present invention is formed by sintering the above conductive paste.

[0136] In one embodiment of the present invention, the temperature of the conductive paste sintering treatment is 700-850°C, preferably 750-800°C.

[0137] Crystalline silicon solar cells

[0138] The present invention also relates to a crystalline silicon solar cell, which comprises a substrate and the electrode combined on the substrate.

[0139] In one embodiment of the present invention, the preferred crystalline silicon solar cell according to the present invention is a crystalline silicon solar cell with high efficiency in terms of the ratio of the total energy of the incident light converted into electrical energy output. Lightweight and durable crystalline silicon solar cells are also preferred. The crystalline silicon solar cell comprises at least: (i) a front electrode, (ii) a front doped layer, (iii) a pn junction boundary, (iv) a back doped layer, (v) a back electrode and (vi) a passivation layer. The crystalline silicon solar cell may also include additional layers for chemical / mechanical protection.

[0140] In one embodiment of the present invention, the crystalline silicon solar cell substrate of the present invention is a substrate for crystalline silicon solar cells known to those skilled in the art.

[0141] The crystalline silicon solar cell of the present invention basically comprises an electrode formed by sintering the conductive paste of the present invention and bonded to the substrate.

[0142] In one embodiment of the present invention, the conductive paste of the present invention is applied to a substrate, such as a semiconductor substrate (eg, a crystalline silicon wafer), to form a printed electrode.

[0143] In one embodiment of the present invention, the electrode is optionally processed by a Laser Enhanced Contact Optimization (LECO) (also known as Laser Assisted Sintering) process.

[0144] The present invention utilizes the characteristics of the laser enhanced contact optimization (LECO) process to repair solar cells with insufficient sintering. The main working principle of LECO is to irradiate the cell with a high-intensity laser to excite charge carriers while applying a reverse voltage of 10V or higher, which will generate a local current of several amperes, causing sintering at the corresponding location.

[0145] In one embodiment of the present invention, the laser enhanced contact optimization (LECO) process comprises the following steps:

[0146] (1) crimping each of the parallel conductive wires onto a main grid line of a solar cell, wherein the conductive wires extend along a first direction of the solar cell, and the first direction is an extension direction of the main grid line;

[0147] (2) providing a power source, electrically connecting a first end of the power source to each conductive wire, and electrically connecting a second end of the power source to a silicon substrate of a solar cell; applying a reverse voltage through the power source solar cell, and the reverse voltage is evenly distributed on the surface of the solar cell through the conductive wire;

[0148] (3) providing a strip-shaped laser spot, wherein the strip-shaped laser spot extends along a second direction of the solar cell, wherein the second direction is an extension direction of the secondary grid line;

[0149] (4) controlling the strip-shaped laser spot to move along a first direction to scan and irradiate the electrodes on the surface of the solar cell, so that the generated radiation current is evenly collected on each main grid line covered by the strip-shaped laser spot;

[0150] (5) After the laser has finished scanning the battery cell, remove the strip laser spot and the conductive wire, remove the battery cell, and proceed to the next battery cell.

[0151] Regarding the laser enhanced contact optimization (LECO) processing process, the contents of CN217485456U are incorporated herein by reference.

[0152] In one embodiment of the present invention, the laser enhanced contact optimization process is processed at a laser wavelength of 400-1500nm (preferably 900-1100nm, such as 1000nm, 1050nm), 500-1100W / cm 2 (Preferably 600-1000nm, for example 600W / cm 2 , 700W / cm 2 , 800W / cm 2 , 900W / cm 2 , 1000W / cm 2 ) and a reverse voltage of 5-40V (preferably 10-25V, for example 10V, 15V, 20V, 25V) for a time of 0.5-5s (for example 0.5s, 0.6s, 0.7s, 0.8s, 0.9s, 1s, 2s, 3s, 4s, 5s) on the entire battery cell.

[0153] The laser may be a laser of any single wavelength / multiple different wavelengths within the above range, or may be a single broad-spectrum laser covering a certain wavelength range within the above range.

[0154] In a preferred embodiment of the present invention, the laser enhanced contact optimization process is performed at a laser wavelength of 1000-1100 nm and a power of 600-1000 W / cm 2 The laser energy density and reverse voltage of 10-25V are carried out on the entire cell for 0.8-1s.

[0155] The conductive paste of the present invention can be applied to the substrate by any method known in the art and considered suitable in the present invention. Examples of such methods include, but are not limited to, dipping, impregnation, pouring, dripping, injection, spraying, blade coating, shower coating, brush coating or printing or a combination of at least two thereof. Preferably, the printing technique is inkjet printing, screen printing, flexographic printing, offset printing, relief printing or stencil printing or a combination of at least two thereof. It is preferred according to the present invention to apply the conductive paste of the present invention by printing, preferably by screen printing.

[0156] Firing is required to sinter the printed electrodes to form a solid conductor. Firing is well known in the art and may be achieved in any manner deemed appropriate in the present invention. It is preferred that firing is performed above the Tg of the glass frit material.

[0157] Outside the area occupied by the electrodes, the substrate of the present invention, preferably a crystalline silicon wafer, has an area where light can be efficiently absorbed to generate electron-hole pairs and efficiently separate holes and electrons across a boundary, preferably a pn junction boundary.

[0158] The pn junction boundary is located where the front doped layer of the wafer meets the back doped layer. In an N-type solar cell, the back doped layer is doped with an n-type dopant and the front doped layer is doped with a p-type dopant. In a P-type solar cell, the back doped layer is doped with a p-type dopant and the front doped layer is doped with an n-type dopant. According to a preferred embodiment of the present invention, a wafer having a pn junction boundary is prepared by first providing a doped silicon substrate and then applying a doped layer of the opposite type to one face of the substrate.

[0159] The above-mentioned dopants are preferably dopants that form pn junction boundaries by introducing electrons or holes into the band structure when added to the crystalline silicon wafer. According to the present invention, it is preferred to specifically select the types and concentrations of these dopants to adjust the band structure profile of the pn junction and set the light absorptivity and conductivity profile as required. The preferred p-type dopant according to the present invention is a dopant that adds holes to the band structure of the crystalline silicon wafer. All dopants known in the art and considered suitable in the present invention can be used as p-type dopants. The preferred p-type dopant according to the present invention is a trivalent element, especially a trivalent element of Group 13 in the periodic table. The preferred Group 13 elements in the periodic table herein include, but are not limited to, boron, aluminum, gallium, indium, thallium or a combination of at least two thereof, of which boron is particularly preferred.

[0160] Preferred n-type dopants according to the present invention are dopants that add electrons to the band structure of the crystalline silicon wafer. All dopants known in the art and considered suitable in the present invention can be used as n-type dopants. Preferred n-type dopants according to the present invention are elements of the fifth group of the periodic table. Preferred elements of the fifth group of the periodic table herein include nitrogen, phosphorus, arsenic, antimony, bismuth or a combination of at least two thereof, wherein phosphorus is particularly preferred.

[0161] In one embodiment of the present invention, according to the present invention, an antireflection layer may be applied as an outer layer before the electrode is applied to the front side of a crystalline silicon solar cell. A preferred antireflection layer according to the present invention is an antireflection layer that reduces the proportion of incident light reflected by the front side and increases the proportion of incident light that will be absorbed by the wafer across the front side. Antireflection layers that produce a favorable absorption ratio / reflection ratio are susceptible to etching by conductive pastes. In addition, antireflection layers that are resistant to the temperatures required for firing the conductive paste and do not promote greater recombination of electrons and holes near the electrode interface are preferred. All antireflection layers known in the art and considered applicable in the present invention can be used. A preferred antireflection layer according to the present invention is silicon nitride, silicon dioxide, aluminum oxide, titanium dioxide, or a mixture of at least two thereof and / or a combination of at least two layers thereof. According to a preferred embodiment, the antireflection layer is silicon nitride, i.e., Si x N y , especially when crystalline silicon wafers are used, wherein x is 2-4 and y is 3-5.

[0162] In one embodiment of the present invention, one or more passivation layers may be applied to the substrate, preferably the front side and / or back side of the crystalline silicon wafer as an outer layer. The passivation layer may be applied before forming the front electrode or before applying the anti-reflection layer (if one of them exists). Preferably, the passivation layer is a passivation layer that reduces the electron / hole recombination rate near the electrode interface. Any passivation layer known in the art and considered applicable in the present invention may be used. According to the present invention, the passivation layer may be silicon nitride, aluminum oxide, silicon dioxide and titanium dioxide. According to the most preferred embodiment, aluminum oxide is used. Preferably, the passivation layer has a thickness of 0.1nm to 2μm, more preferably 1nm to 1μm, and most preferably 1nm to 200nm.

[0163] In one embodiment of the present invention, in addition to the above-mentioned layers which directly contribute to the main functions of the crystalline silicon solar cell, further layers may be added for mechanical and chemical protection.

[0164] The battery can be encapsulated to provide chemical protection. Encapsulation is well known in the art and any encapsulation suitable for the present invention can be used. According to a preferred embodiment, a transparent polymer (commonly referred to as a transparent thermoplastic resin) is used as an encapsulation material, provided that such an encapsulation exists. Preferred transparent polymers herein are silicone rubber and polyethylene vinyl acetate (EVA).

[0165] A transparent glass sheet may also be added to the front side of the crystalline silicon solar cell to provide mechanical protection thereto. Transparent glass sheets are well known in the art, and any transparent glass sheet suitable for use in the present invention may be employed.

[0166] A back protective material can be added to the back of the crystalline silicon solar cell to provide mechanical protection. Back protective materials are well known in the art, and any back protective material deemed suitable in the present invention can be used. A preferred back protective material according to the present invention is a back protective material with good mechanical properties and weather resistance. A preferred back protective material according to the present invention is polyethylene terephthalate with a polyvinyl fluoride layer (e.g., a PTFE layer). It is preferred according to the present invention that the back protective material is present below the encapsulation layer (in the presence of a back protective layer and an encapsulation).

[0167] Frame materials may be added to the outside of the crystalline silicon solar cell to impart mechanical support. Frame materials are well known in the art and any frame material deemed suitable for use in the present invention may be employed. A preferred frame structure according to the present invention is aluminum.

[0168] In a preferred embodiment of the present invention, the conductive paste of the present invention is used to prepare an N-type solar cell, in particular a TOPCon solar cell, and the conductive paste comprises:

[0169] a) 50-95% by weight of conductive metal particles,

[0170] b) 1-15% by weight of glass powder,

[0171] c) 0.1-10 wt% of a laser thermal accelerator, and

[0172] d) 2-20% by weight of an organic carrier,

[0173] The weight percentage is based on the total weight of the conductive paste.

[0174] Those skilled in the art can more easily understand the present invention according to the following embodiments:

[0175] Embodiment 1. A conductive paste comprising:

[0176] a) Conductive metal particles,

[0177] b) glass powder,

[0178] c) laser thermal accelerator, and

[0179] d) an organic carrier,

[0180] The laser thermal accelerator is represented by formula (I):

[0181] Zrx Cu y Al m Ni z Nb n A q (I)

[0182] In formula (I), x=10-90 wt%, y=5-50 wt%, m=0.5-10 wt%, z=0-20 wt%, n=0-15 wt%, q=0-5 wt%, and A is a metal selected from Ag, Cr, Zn and Ti, and the weight percentages are based on the weight of the laser thermal accelerator.

[0183] Embodiment 2. The conductive paste according to embodiment 1, wherein in formula (I), x=50-90 wt % and y=5-35 wt %.

[0184] Embodiment 3. The conductive paste according to embodiment 1 or 2, wherein the laser thermal accelerator is amorphous metal alloy particles.

[0185] Embodiment 4. The conductive paste according to any one of embodiments 1 to 3, wherein the laser thermal accelerator has a particle size D50 of 0.1-8 μm, preferably 1-5 μm.

[0186] Embodiment 5. The conductive paste according to any one of embodiments 1 to 4, wherein the conductive metal particles comprise Ag, Al, Cu, Zn, Pd, Ni, Pb, Au or a combination thereof, preferably Ag, Al, Cu or an alloy thereof, more preferably Ag.

[0187] Embodiment 6. The conductive paste according to any one of embodiments 1 to 5, wherein the conductive metal particles have a particle size D50 of 0.5-10 μm, preferably 1-5 μm.

[0188] Embodiment 7. A conductive paste according to any one of embodiments 1 to 6, wherein the glass powder comprises oxides of elements selected from Si, B, Al, Bi, Li, Na, K, Mg, Pb, Zn, Gd, Ce, Zr, Ti, Mn, Sn, Ru, Co, Fe, Cu, Ba, Cr, Te, P and combinations thereof, preferably comprising PbO, B2O3, SiO2, ZnO, Al2O3, TeO2, Bi2O3, P2O5 or a combination of any two or more thereof.

[0189] Embodiment 8. The conductive paste according to any one of embodiments 1 to 7, wherein the glass powder has a glass transition temperature Tg of 300-600°C, preferably 300-500°C.

[0190] Embodiment 9. The conductive paste according to any one of Embodiments 1 to 8, wherein the glass powder has a particle size D50 of 0.1-10 μm, preferably 0.2-7 μm, and more preferably 0.5-5 μm.

[0191] Embodiment 10. The conductive paste according to any one of embodiments 1-9, wherein in formula (I),

[0192] (1) n = 1-10% by weight, or

[0193] (2) n = 1-10 wt% and z = 8-15 wt%, or

[0194] (3) z=8-15 wt%, q=1-5% and A is Ti.

[0195] Embodiment 11. The conductive paste according to any one of embodiments 1-10, wherein the conductive paste comprises:

[0196] a) 50-95% by weight of conductive metal particles,

[0197] b) 0.1-15% by weight of glass powder,

[0198] c) 0.1-10 wt% of a laser thermal accelerator, and

[0199] d) 2-20% by weight of an organic carrier,

[0200] The weight percentages are based on the total weight of the conductive paste.

[0201] Embodiment 12. An electrode for a crystalline silicon solar cell, wherein the electrode is formed by sintering the conductive paste described in any one of Embodiments 1 to 11.

[0202] Embodiment 13. The electrode according to embodiment 12 is processed by a laser enhanced contact optimization process, wherein the laser enhanced contact optimization process is processed at a laser wavelength of 400-1500nm and a power of 500-1100W / cm 2 The laser energy density and reverse voltage are 5-40V.

[0203] Embodiment 14. An electrode according to embodiment 13, wherein the reverse voltage is 10-25V.

[0204] Embodiment 15. A crystalline silicon solar cell, comprising a substrate and the electrode described in any one of Embodiments 12 to 14 bonded to the substrate, wherein the crystalline silicon solar cell is an N-type crystalline silicon solar cell, preferably a TOPCon solar cell.

[0205] Example

[0206] The present invention is illustrated below by way of example, but it should be understood that the following examples are non-limiting and are not intended to limit the scope of protection of the present invention.

[0207] raw material

[0208] PbO, B2O3, SiO2, ZnO, Al2O3, TeO2, Bi2O3, and P2O5 are 4N grade chemical reagents.

[0209] Silver powder (Ag) and aluminum powder (Al) are spherical powders with a particle size D50 of 2 μm.

[0210] The silicon wafer is an N-type silicon wafer with a size of 182mm and a silicon nitride and aluminum oxide passivation layer.

[0211] The organic carrier (V1) is composed as follows:

[0212] Diethylene glycol butyl ether acetate: 5.6 parts by weight;

[0213] Cellulose acetate butyrate: 0.6 parts by weight;

[0214] Oleic acid: 0.6 parts by weight;

[0215] Hydrogenated castor oil: 0.6 parts by weight;

[0216] Alkyl-modified silicone oil: 0.6 parts by weight.

[0217] The composition of the glass powder (G1-G5) is shown in Table 1 below:

[0218] Table 1 Composition of glass powder

[0219] Mole % G1 G2 G3 G4 G5 PbO 40% 25% 30% 40% <![CDATA[B2O3]]> 10% 15% 10% <![CDATA[SiO2]]> 50% 45% 5% 5% 42% ZnO 5% 15% 5% 15% <![CDATA[Al2O3]]> 5% <![CDATA[TeO2]]> 50% 50% <![CDATA[Bi2O3]]> 5% 30% <![CDATA[P2O5]]> 3% total 100% 100% 100% 100% 100%

[0220] The compositions of the laser thermal accelerators (LTP) (AM01-AM04) are shown in Table 2 below:

[0221] Table 2 Composition of laser thermal promoter (LTP)

[0222] weight% AM01 AM02 AM03 AM04 Zr 69 70 64 70 Cu 20 16 15 12 Al 8 8 5 3 Nb 3 6 5 Ni 12 10 Ti 4 total 100% 100% 100% 100%

[0223] Test Method

[0224] The commercial IV tester “cetisPV-Celltest4-BF” from Halm Elektronik GmbH was used to conduct IV experiments on the cells to measure the cell conversion efficiency (Eta), open circuit voltage (Voc), short circuit current (Isc), fill factor (FF), and series resistance (Rs).

[0225] Preparation of glass powder

[0226] Weigh the components of glass powders G1 to G5 according to the ratios shown in Table 1, respectively, and combine them together to obtain compositions corresponding to glass powders G1 to G5;

[0227] The obtained compositions were respectively loaded into alumina crucibles, placed in a muffle furnace and kept at 1100° C. for 60 minutes;

[0228] The alumina crucibles containing the molten glass were removed from the muffle furnace, and the molten glass was poured into a bucket containing deionized water for water quenching;

[0229] The water-quenched glass slag was respectively ground into a particle size D50 of about 1.5 μm using a ball mill, thereby obtaining glass powders G1 to G5.

[0230] Preparation of Laser Thermal Promoter (LTP)

[0231] The laser thermal accelerator is prepared by a jet powder preparation method, which includes the following steps:

[0232] (1) High-purity metal powders (purity 99%) used to prepare laser thermal accelerators were mixed and dispersed uniformly according to the formula ratio in Table 2;

[0233] (2) heating and melting the obtained metal powder mixture in a copper pressure crucible lined with quartz at a temperature of 1100° C. to obtain a liquid master alloy;

[0234] (3) The liquid master alloy was directly sprayed into ice water mixed with 2 wt % NaCl under a pressure of 50 PSI to produce amorphous LTP alloy powder.

[0235] Preparation of Conductive Paste (Examples 1-4 / Comparative Example 1)

[0236] Silver powder, laser thermal accelerator (LTP) or aluminum powder, glass powder and organic carrier were weighed respectively according to the ratio shown in Table 3, combined, mixed with a planetary mixer, and then mixed with a three-roll grinder to prepare the conductive paste of Examples 1-4 / Comparative Example 1.

[0237] Table 3 Composition of conductive paste

[0238]

[0239] Preparation of solar cell substrate with electrodes (Samples 1-4 of the present invention / Comparative sample 1)

[0240] The conductive pastes of Examples 1-4 were respectively printed onto N-type silicon wafers by screen printing (430-11-15-3.5-14-9BB screen), and then rapidly sintered at a peak temperature of 750°C and a time from room temperature to peak temperature of 16 seconds, and then subjected to a laser enhanced contact optimization (LECO) process (laser wavelength of 1064 nm, laser energy density of 800 W / cm 2 , LECO reverse voltage is 14V, laser processing time is 0.8s), a solar cell substrate with an electrode (samples 1-4 of the present invention) was prepared, and the electrical properties were tested. The results are shown in Table 4.

[0241] The conductive paste of Comparative Example 1 was printed onto an N-type silicon wafer by screen printing (430-11-15-3.5-14-9BB screen), and then rapidly sintered (conventional sintering) under the conditions of a peak temperature of 800°C and a time from room temperature to peak temperature of 16 seconds to obtain a solar cell substrate with electrodes (Comparative Sample 1), and the electrical properties were tested. The results are shown in Table 4.

[0242] Table 4 Performance of solar cells

[0243]

[0244]

[0245] The results in Table 4 show that the cell conversion efficiency (Eta), fill factor (FF) and resistance (Rs) of the solar cell of the present invention are improved in the sample of the present invention using the laser thermal promoter of the present invention compared to the control sample using aluminum powder. The reduction of Rs indicates the reduction of the contact resistance of the solar cell of the present invention.

[0246] Preparation of conductive paste (Examples 5-8)

[0247] Silver powder, laser thermal accelerator (LTP), glass powder and organic vehicle were weighed respectively according to the ratio shown in Table 5, combined, mixed with a planetary mixer, and then mixed with a three-roll mill to prepare the conductive pastes of Examples 5-8.

[0248] Table 5 Composition of conductive paste

[0249]

[0250] Preparation of solar cell substrate with electrodes (Samples 5-8 of the present invention)

[0251] The conductive pastes of Examples 5-8 were respectively printed onto N-type silicon wafers by screen printing (430-11-15-3.5-14-9BB screen), and then rapidly sintered at a peak temperature of 750°C and a time from room temperature to peak temperature of 16 seconds, and then subjected to a laser enhanced contact optimization (LECO) process (laser wavelength of 1064 nm, laser energy density of 800 W / cm 2 , LECO reverse voltage is 14V, laser processing time is 0.8s), a solar cell substrate with an electrode (samples 5-8 of the present invention) was prepared, and the electrical properties were tested. The results are shown in Table 6.

[0252] Table 6 Performance of solar cells

[0253]

[0254] The results in Table 6 show that the cell conversion efficiency (Eta), fill factor (FF) and resistance (Rs) of the solar cell of the present invention are improved in the samples of the present invention using the laser thermal promoter of the present invention and glass powder of different compositions compared with the control samples using aluminum powder. The reduction in Rs indicates a reduction in the contact resistance of the solar cell of the present invention.

[0255] Preparation of conductive paste (Comparative Example 2)

[0256] The conductive paste of Comparative Example 2 was prepared in the same manner as the conductive paste of Example 2, except that aluminum powder was used instead of the laser thermal accelerator in Example 2.

[0257] Preparation of solar cell substrate with electrodes (Samples 9-12 of the present invention / Comparative sample 2)

[0258] The conductive paste of Example 2 was printed onto four N-type silicon wafers by screen printing (430-11-15-3.5-14-9BB screen), and then quickly sintered under the conditions of a peak temperature of 750°C and a time of 16 seconds from room temperature to peak temperature. The four sintered N-type silicon wafers were then subjected to different laser enhanced contact optimization (LECO) processes (as shown in Table 7) to obtain solar cell substrates with electrodes (samples 9-12 of the present invention).

[0259] The conductive paste of Comparative Example 2 was printed onto an N-type silicon wafer by screen printing (430-11-15-3.5-14-9BB screen), and then rapidly sintered under the conditions of a peak temperature of 750°C and a time of 16 seconds from room temperature to peak temperature. The sintered N-type silicon wafer was then subjected to a laser enhanced contact optimization (LECO) process (as shown in Table 7) to obtain a solar cell substrate with an electrode (Comparative Sample 2).

[0260] Table 7 Manufacturing conditions of solar cells

[0261]

[0262] The electrical performance test results of samples 9-12 of the present invention and comparative samples 1-2 are shown in Table 8.

[0263] Table 8 Performance of solar cells

[0264]

[0265]

[0266] The results of Table 8 show that the sample of the present invention using the laser thermal accelerator of the present invention has improved cell conversion efficiency (Eta), fill factor (FF) and resistance (Rs) of the solar cell of the present invention relative to comparative sample 1 using aluminum powder (not subjected to LECO process treatment), and the reduction of Rs indicates the reduction of contact resistance of the solar cell of the present invention. The sample of the present invention using the laser thermal accelerator of the present invention has a higher cell conversion efficiency (Eta) of the solar cell of the present invention relative to comparative sample 2 using aluminum powder (treated with LECO process).

Claims

1. A conductive paste comprising: a) 50-95% by weight of conductive metal particles, b) 0.1-15% by weight of glass powder, c) 0.1-10 wt% of a laser thermal accelerator, and d) 2-20% by weight of an organic carrier, The weight percentage is based on the total weight of the conductive paste. The laser thermal accelerator is represented by formula (I): Zr x Cu y Al m Ni z No n A q (I) In formula (I), x=50-90 wt%, y=5-35 wt%, m=0.5-10 wt%, z=0-20 wt%, n=0-15 wt%, q=0-5 wt%, and A is a metal selected from Ag, Cr, Zn and Ti, and the weight percentages are based on the weight of the laser thermal accelerator. 2 . The conductive paste according to claim 1 , wherein the laser thermal accelerator is amorphous metal alloy particles. 3 . The conductive paste according to claim 1 , wherein the laser thermal accelerator has a particle size D50 of 0.1-8 μm. 4 . The conductive paste according to claim 2 , wherein the laser thermal accelerator has a particle size D50 of 0.1-8 μm. 5 . The conductive paste according to claim 3 , wherein the laser thermal accelerator has a particle size D50 of 1-5 μm.

6. The conductive paste according to any one of claims 1 to 4, wherein the conductive metal particles comprise Ag, Al, Cu, Zn, Pd, Ni, Pb, Au or a combination thereof. The conductive paste according to claim 6 , wherein the conductive metal particles comprise Ag, Al, Cu or alloys thereof. The conductive paste according to claim 6 , wherein the conductive metal particles comprise Ag.

9. The conductive paste of claim 5, wherein the conductive metal particles comprise Ag, Al, Cu, Zn, Pd, Ni, Pb, Au, or a combination thereof.

10. The conductive paste according to any one of claims 1 to 4, wherein the conductive metal particles have a particle size D50 of 0.5 to 10 μm. The conductive paste according to claim 10 , wherein the conductive metal particles have a particle size D50 of 1-5 μm. 12 . The conductive paste according to claim 9 , wherein the conductive metal particles have a particle size D50 of 0.5-10 μm.

13. The conductive paste according to any one of claims 1 to 4, wherein the glass powder comprises an oxide of an element selected from the group consisting of Si, B, Al, Bi, Li, Na, K, Mg, Pb, Zn, Gd, Ce, Zr, Ti, Mn, Sn, Ru, Co, Fe, Cu, Ba, Cr, Te, P, and combinations thereof. 14 . The conductive paste according to claim 13 , wherein the glass frit comprises PbO, B 2 O 3 , SiO 2 , ZnO, Al 2 O 3 , TeO 2 , Bi 2 O 3 , P 2 O 5 , or a combination of any two or more thereof.

15. The conductive paste of claim 12, wherein the glass frit comprises an oxide of an element selected from the group consisting of Si, B, Al, Bi, Li, Na, K, Mg, Pb, Zn, Gd, Ce, Zr, Ti, Mn, Sn, Ru, Co, Fe, Cu, Ba, Cr, Te, P, and combinations thereof.

16. The conductive paste according to any one of claims 1 to 4, wherein the glass frit has a glass transition temperature Tg of 300-600°C. 17 . The conductive paste according to claim 16 , wherein the glass frit has a glass transition temperature Tg of 300-500° C.

18. The conductive paste according to claim 15, wherein the glass frit has a glass transition temperature Tg of 300-600°C.

19. The conductive paste according to any one of claims 1 to 4, wherein the glass powder has a particle size D50 of 0.1 to 10 μm. 20 . The conductive paste according to claim 19 , wherein the glass powder has a particle size D50 of 0.2-7 μm. 21 . The conductive paste according to claim 19 , wherein the glass frit has a particle size D50 of 0.5-5 μm. 22 . The conductive paste according to claim 18 , wherein the glass frit has a particle size D50 of 0.1-10 μm.

23. The conductive paste according to any one of claims 1 to 4, wherein in formula (I), (1) n = 1-10% by weight, or (2) n = 1-10 wt% and z = 8-15 wt%, or (3) z=8-15 wt%, q=1-5% and A is Ti.

24. The conductive paste according to claim 22, wherein in formula (I), (1) n = 1-10% by weight, or (2) n = 1-10 wt% and z = 8-15 wt%, or (3) z=8-15 wt%, q=1-5% and A is Ti.

25. An electrode for a crystalline silicon solar cell, the electrode being formed by sintering the conductive paste according to any one of claims 1 to 24.

26. The electrode according to claim 25, wherein the electrode is processed by a laser enhanced contact optimization process, wherein the laser enhanced contact optimization process is processed at a laser wavelength of 400-1500nm, 500-1100W / cm 2 The laser energy density and reverse voltage are 5-40V.

27. The electrode according to claim 26, wherein the reverse voltage is 10-25V.

28. A crystalline silicon solar cell, comprising a substrate and the electrode according to any one of claims 25 to 27 bonded to the substrate, wherein the crystalline silicon solar cell is an N-type crystalline silicon solar cell.

29. The crystalline silicon solar cell according to claim 28, wherein the crystalline silicon solar cell is a TOPCon solar cell.

Citation Information

Patent Citations

  • Silver conductive paste used for positive electrode of solar battery and preparation technique thereof

    CN101609849A

  • Preparation method of solar cell and solar cell

    CN115312629A

  • Equipment for reducing contact resistance of crystalline silicon solar cell

    CN217485456U

  • Conductive paste for fine-line high-aspect-ratio screen printing in the manufacture of semiconductor devices

    US20130180583A1

  • Conductive paste, and electronic device and solar cell including an electrode formed using the conductive paste

    US20120048363A1